Mood disorders in patients with neuropsychological disorders: an integrative literature review (Research, Society and Development, 2022)
The aim of this study was to analyze the scientific contributions on symptoms of mood disorders in patients with neuropsychological alterations, in national and international scope. An Integrative Literature Review was carried out, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), through the following electronic databases: Scopus, PubMed, Web of Science, Portal BVS and PsyNet, using the descriptors: “mood” and “neuropsychological disorder” or “neuropsychological disease” or “neuropsychological disturb”. After applying the inclusion and exclusion criteria, 42 articles were selected, 24 on mood disorders (bipolar, depression, impulsiveness, anhedonia, anxiety, insecurity, hopelessness, and affectivity) and 18 on neuropsychological disorders (multiple sclerosis, dementia, Parkinson's disease, Alzheimer's disease, Schizophrenia, vascular and cardiovascular disease). The results showed the importance of deepening the investigations related to mood disorders and neuropsychological alterations, since they negatively impact the individual's life, with emphasis on the cognitive sphere and executive functions, which are essential for well-being and coexistence Social.